PENGARUH PEMANFAATAN CSR BANK INDONESIA TERHADAP MINAT BACA DAN PRESTASI AKADEMIK MAHASISWA PERBANKAN SYARIAH TAHUN 2014 FAKULTAS SYARIAH DAN EKONOMI ISLAM - Wike Pertiwi; Ghina Aulia (Jurnal Ekonomi Manajemen, 2019)
ABSTRACTA Student achievement is a reflection of the students‟ potential that influenced by the quality of teaching and learning process. It makes the utilization of CSR BI (BI Corner) in increasing reading interest and student academic achievement is needed. This study used a quantitative approach with the type of causality research. This study used a sample of 71 people from a population of 251 people using a slovin formula. Primary data were analyzed by using hypothesis with validity test, reliability, classical assumption (NOR) and significance test. Data processing techniques used simple linear regression. The results of this study reveal that there is a significant influence between the utilization of Corporate Social Responsibility (CSR) to the Reading Interests Variable (Y1) and the significant influence the utilization of Corporate Social Responsibility (CSR) to Academic Achievement variables (Y2) and there is a strong relationship between Reading Interests (Y1) and Academic Achievement (Y2).ABSTRAKPrestasi mahasiswa merupakan pencerminan dari potensi mahasiswa itu sendiri yang dipengaruhi oleh kualitas proses belajar mengajar (PBM). Hal ini menjadikan pemanfaatan CSR Bank Indonesia (BI Corner) dalam meningkatkan minat baca dan prestasi akademik mahasiswa sangat dibutuhkan. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian kausalitas. Sampel sebanyak 71 orang dari populasi 251 mahasiswa. Teknik analisis data menggunakan regresi linier sederhana dan korelasi sederhana.Hasil penelitian ini adalah 1) adanya pengaruh yang signifikan antara pemanfaatan Corporate Social Responsibility (CSR) terhadap variabel Minat Baca (Y1), dan 2) pengauh yang signifikan pemanfaatan Corporate Social Responsibility (CSR) terhadap variabel Prestasi Akademik (Y2), serta 3) terdapat hubungan yang kuat antara Minat Baca (Y1) dengan Prestasi Akademik (Y2)